A carbon-coated lithium manganese iron phosphate positive electrode material and its preparation method and application

By using biomass furfural slag activated carbon for carbon coating and using ferromanganese phosphate as raw material to prepare lithium ferromanganese phosphate positive electrode material, the problems of insufficient improvement in electrical conductivity and electrochemical properties of existing materials, low purity and high cost are solved, and high performance and low cost preparation of positive electrode material is achieved.

CN119742344APending Publication Date: 2025-04-01HENAN LONGBAI NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411936171.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have no obvious improvement in electrical conductivity and electrochemical properties after carbon coating, and the material is low in purity and high in cost.

Method used

Biomass furfural slag activated carbon is used as the carbon coating material, and lithium manganese phosphate phosphate is prepared by low-temperature carbonization and high-temperature activation treatment, combined with ferromanganese phosphate as raw material, and high-temperature solid phase method is used to prepare lithium manganese phosphate positive electrode material.

Benefits of technology

The conductivity and electrochemical properties of lithium manganese iron phosphate cathode material are improved, the rate performance and cyclic properties are enhanced, the production cost is reduced, and the purity and particle uniformity of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a carbon-coated lithium iron manganese phosphate positive electrode material and a preparation method and application thereof, and relates to the technical field of lithium ion batteries. Specifically, furfural slag is sequentially subjected to low-temperature carbonization and high-temperature activation to obtain a first carbon source; a mixed solution containing the first carbon source and the second carbon source is prepared, ground and obtained a carbon dispersion; a mixed solution containing the carbon dispersion, iron manganese phosphate and a lithium source is prepared, ground and obtained a slurry; the slurry is sequentially spray-dried, sintered and crushed to obtain a lithium iron manganese phosphate positive electrode material. The present invention uses furfural slag as a raw material to prepare a new type of biomass activated carbon as a coating material, which is cross-linked with another carbon source to form a conductive network structure between lithium iron manganese phosphate particles, which effectively improves the electronic conductivity of lithium iron manganese phosphate; at the same time, the positive electrode material of the present invention also has good electrochemical properties, the preparation method is simple and easy, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-coated lithium manganese iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium manganese iron phosphate (LiFeMnPO4, LMFP for short) is a high-performance cathode material with broad application prospects in the field of lithium-ion batteries. With the rapid growth of the electric vehicle and portable electronic device markets, the demand for high-performance, high-energy-density and long-life lithium-ion batteries is increasing; LMFP is regarded as a potential alternative to traditional cathode materials such as lithium cobalt oxide (LiCoO2) and lithium iron phosphate (LiFePO4) due to its high energy density, good cycle stability and safety. However, LMFP itself has poor electronic conductivity and slow ion diffusion kinetics, which not only affects the battery's charge and discharge rate, but also limits its application as a battery cathode material.

[0003] In order to improve the electrochemical performance of LMFP, LMFP is usually modified by means of particle refinement, surface carbon coating and ion doping. Among them, surface carbon coating materials such as carbon nanotubes and graphene have high conductivity, which can effectively improve the conductivity of LMFP, thereby reducing the internal resistance of the battery and improving the overall performance of the battery; at the same time, the carbon coating layer hinders the direct contact between material particles to a certain extent, and can effectively inhibit the growth and agglomeration of particles. However, relying solely on simple coated carbon materials cannot obtain LMFP positive electrode materials with ideal performance, and the current technology for carbon coating of LMFP is relatively simple and costly, and cannot guarantee a complete carbon coating structure; in addition, the conductive network between carbon-coated LMFP is missing, which makes the conductivity of LMFP not significantly improved, and the rate performance and cycle performance are not significantly improved.

[0004] In addition, common preparation processes of LMFP include solid phase method, coprecipitation method, hydrothermal method, sol-gel method, etc. Among them, the high temperature solid phase method has been widely used on a large scale due to its mature process and low cost. The high temperature solid phase method is usually used to prepare LMFP positive electrode materials using oxides or phosphates of manganese, iron and lithium as raw materials; however, the solid phase raw materials used often contain impurities, and the high temperature solid phase method itself is difficult to control, which leads to the easy production of by-products, which reduces the purity of the LMFP products obtained by the high temperature solid phase method, thereby affecting its preparation efficiency and electrochemical performance.

[0005] Therefore, it is of great significance to provide a new type of carbon-coated lithium manganese iron phosphate positive electrode material with high purity and low cost; in view of this, the present invention is specially proposed. Summary of the invention

[0006] The first purpose of the present invention is to provide a method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material, which is used to solve the defects of conventional lithium manganese iron phosphate, such as the lack of obvious improvement in conductivity and electrochemical performance when carbon-coated, low material purity and high cost.

[0007] The second object of the present invention is to provide a lithium manganese iron phosphate positive electrode material having good electrical conductivity and electrochemical properties, and having good particle uniformity and crystal purity.

[0008] A third object of the present invention is to provide a lithium ion battery.

[0009] A fourth object of the present invention is to provide an electrical device.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material comprises the following steps:

[0012] (1) subjecting furfural residue to low-temperature carbonization and high-temperature activation in sequence to obtain a first carbon source;

[0013] (2) preparing a mixed solution comprising the first carbon source and the second carbon source, grinding and obtaining a carbon dispersion;

[0014] (3) preparing a mixed solution comprising the carbon dispersion, ferromanganese phosphate and a lithium source, grinding and obtaining a slurry;

[0015] (4) The slurry is spray-dried, sintered and crushed in sequence to obtain a lithium manganese iron phosphate positive electrode material.

[0016] A lithium iron manganese phosphate positive electrode material is prepared based on the preparation method of the carbon-coated lithium iron manganese phosphate positive electrode material.

[0017] A lithium ion battery comprises the lithium iron manganese phosphate positive electrode material.

[0018] An electrical device comprises the lithium-ion battery.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention adopts a new type of biomass furfural slag activated carbon to prepare lithium iron manganese phosphate positive electrode material through a carbon coating process. The furfural slag activated carbon prepared by the resource-based treatment method of the present invention has a high degree of graphitization, a high specific surface area and an electron transfer rate, can provide more electron and ion transfer sites during the charge and discharge process, and can effectively improve the electron transfer rate of the lithium iron manganese phosphate positive electrode material. In addition, during coating, the furfural slag activated carbon is cross-linked with another carbon source used in the present invention to form a conductive network structure between the lithium iron manganese phosphate particles, which can improve the overall electron conductivity of the carbon-coated lithium iron manganese phosphate positive electrode material, thereby improving its rate performance and cycle performance as a positive electrode material, and achieving the purpose of improving the current carbon coating technology to improve the conductivity and electrochemical performance.

[0021] (2) The present invention uses manganese ferrophosphate Fe x Mn y PO4 is used as the raw material as the iron source, manganese source and phosphorus source to prepare lithium iron manganese phosphate positive electrode material, which replaces the previous addition of manganese and iron oxides or phosphates as raw materials. Compared with other raw material addition methods, ferromanganese phosphate is relatively easy to obtain and has a lower cost; at the same time, the use of ferromanganese phosphate as a raw material in the process of synthesizing lithium iron manganese phosphate positive electrode material reduces the negative impact on the environment and generates less waste and wastewater; most importantly, the lithium iron manganese phosphate positive electrode material synthesized with ferromanganese phosphate as the raw material has high purity, more uniform particle size and purer crystal structure, which helps to improve its electrochemical performance as a positive electrode material, achieving the purpose of improving the low purity of the current lithium iron manganese phosphate positive electrode material.

[0022] (3) The novel biomass activated carbon-coated lithium iron manganese phosphate positive electrode material provided by the present invention has a simple and easy-to-operate preparation method and low cost. Moreover, the raw materials biomass activated carbon and ferromanganese phosphate used are low-cost, easy to obtain, and easy to scale industrial production. Under the premise of satisfying the electrochemical properties of the positive electrode material such as rate performance and cycle performance, the purpose of improving the high cost of the current lithium iron manganese phosphate positive electrode material is achieved, and it has good application prospects. DETAILED DESCRIPTION

[0023] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will appreciate that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. Those who do not specify specific conditions in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be purchased commercially. In addition, the terms "first", "1", "2", etc. are only used for descriptive purposes and cannot be interpreted as indicating or suggesting relative importance.

[0024] The first aspect of the present invention is to provide a method for preparing a carbon-coated lithium iron manganese phosphate positive electrode material, which mainly includes the following steps (1) to (5); the main preparation route of the present invention includes: first preparing a specific biomass activated carbon using furfural residue as a raw material, mixing it with the current conventional electrode carbon source, and then mixing it with iron manganese phosphate and lithium for a second time, and preparing a new biomass activated carbon-carbon-coated lithium iron manganese phosphate positive electrode material by a high-temperature solid phase method.

[0025] (1) The furfural residue is subjected to low-temperature carbonization and high-temperature activation in sequence to obtain a first carbon source.

[0026] Furfural residue is a biomass waste produced in the process of hydrolyzing the polypentose components in the processing waste materials of biomass materials (such as corn cobs, corn stalks, rice husks, cottonseed hulls and other agricultural and sideline products) to produce furfural (furan formaldehyde). It is usually directly burned and cannot be effectively utilized. In addition, furfural residue has a high carbon content and contains a large amount of cellulose and lignin, which is a good raw material for preparing activated carbon. The resource utilization of waste is achieved through the characteristic treatment process in this step, and a carbon-coated material with a high degree of graphitization, a high specific surface area and a conductive effect is obtained.

[0027] As a preferred embodiment, the low-temperature carbonization is carried out in an inert gas atmosphere, and the inert gas includes but is not limited to one or more of nitrogen, helium, krypton, xenon, neon, argon and radon.

[0028] As a preferred embodiment, the low-temperature carbonization temperature is 420°C to 480°C, and the low-temperature carbonization time is 45min to 80min; in some optional embodiments, the low-temperature carbonization temperature includes but is not limited to any one of 420, 430, 440, 450, 460, 470, 480 (°C) or a numerical range formed by any two of them, and the low-temperature carbonization time includes but is not limited to any one of 45, 50, 55, 60, 65, 70, 75, 80 (min) or a numerical range formed by any two of them.

[0029] As a preferred embodiment, the high temperature activation temperature is 900°C to 950°C, and the high temperature activation time is 45min to 80min; in some optional embodiments, the high temperature activation temperature includes but is not limited to any one of 900, 905, 910, 915, 920, 925, 930, 935, 940, 945, 950 (°C) or a numerical range composed of any two of them, and the high temperature activation time includes but is not limited to any one of 45, 50, 55, 60, 65, 70, 75, 80 (min) or a numerical range composed of any two of them.

[0030] As a preferred embodiment, the high-temperature activation comprises: placing the material after the low-temperature carbonization in a superheated steam atmosphere and letting it stand; in some more preferred embodiments, the carbon-to-water ratio of the high-temperature activation is 1:(4-5) by mass, and the water in the carbon-to-water ratio refers to the amount of water used to generate water vapor.

[0031] As a preferred embodiment, the first carbon source (also understood as furfural residue activated carbon) obtained in this step includes at least one of the following properties: a) I G / I D is 1.0~1.2; b) specific surface area is 500m 2 / g~800m 2 / g; c) the electron migration rate is 10 3 S / m~10 6 S / m.

[0032] (2) preparing a mixed solution containing the first carbon source and the second carbon source, grinding and obtaining a carbon dispersion.

[0033] As a preferred embodiment, the second carbon source includes at least one of glucose, sucrose, fructose, polyvinyl alcohol, polyethylene glycol, aspartic acid, citric acid and β-cyclodextrin.

[0034] As a preferred embodiment, the solvent of the mixed solution in steps (2) to (3) is at least one of pure water, ethanol, methanol and acetone, and the solvents in the two steps are selected independently. Those skilled in the art can select the same or different solvent components based on the above examples.

[0035] As a preferred embodiment, the usage ratio of the first carbon source to the second carbon source is (0.2-0.8):1 by mass, including but not limited to any one of 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1 or a ratio interval consisting of any two of them.

[0036] As a preferred embodiment, the grinding in steps (2) to (3) can be carried out by methods such as ball milling, vibration milling, etc., which can not only mix the raw materials evenly, but also refine the particle size of the raw materials, thereby facilitating the acquisition of positive electrode materials with stable properties.

[0037] As a preferred embodiment, the grinding time in this step is 30 min to 60 min.

[0038] (3) preparing a mixed solution comprising the carbon dispersion, ferromanganese phosphate and a lithium source, grinding and obtaining a slurry.

[0039] As a preferred embodiment, based on the total carbon content in the carbon dispersion, the carbon source in the carbon dispersion is 15 wt.% to 25 wt.% of the added amount of the ferromanganese phosphate.

[0040] As a preferred embodiment, the lithium source includes at least one of lithium carbonate, lithium phosphate, lithium hydroxide, lithium sulfate, lithium acetate, lithium dihydrogen phosphate, lithium nitrate and lithium acetate.

[0041] As a preferred embodiment, the molecular formula of the ferromanganese phosphate is Fe x Mn y PO4, 0.3≤x≤0.7, 0.3≤y≤0.7, x+y=1.

[0042] The lithium iron manganese phosphate positive electrode material synthesized by using iron manganese phosphate as a raw material has a more uniform particle size and a purer crystal structure, which helps to improve its rate performance and cycle performance as a positive electrode material.

[0043] As a preferred embodiment, the molar ratio of the iron element, the manganese element, the phosphorus element in the ferromanganese phosphate and the lithium element in the lithium source is (0.3-0.7): (0.3-0.7): 1:1.

[0044] As a preferred embodiment, the solid content of the mixed solution in this step is 35wt.% to 45wt.%.

[0045] As a preferred embodiment, the grinding time in this step is 3h to 5h.

[0046] As a preferred embodiment, the average particle size D50 of the slurry is 0.35 μm to 0.45 μm.

[0047] (4) The slurry is spray-dried, sintered and crushed in sequence to obtain a lithium manganese iron phosphate positive electrode material.

[0048] As a preferred embodiment, the inlet air temperature of the spray drying is 210°C to 250°C, and the outlet air temperature of the spray drying is 90°C to 100°C.

[0049] As a preferred embodiment, the sintering is a two-stage process, firstly heating to 400-600°C at 1-3°C / min, keeping the temperature for 2-5h, and then heating to 700-800°C at 5-10°C / min, keeping the temperature for 7-10h.

[0050] The present invention preferably adopts a two-stage high-temperature sintering method to prepare the lithium iron manganese phosphate positive electrode material. The first stage of temperature rise sintering causes the particles to crystallize and nucleate to form primary particles. These particles are usually small in size, providing a basis for the particle size of the final lithium iron manganese phosphate positive electrode material; the second stage of temperature rise sintering causes the particles to grow further, densifying the material and forming a good crystal structure. The sintering method of the present invention not only improves the integrity of the crystal structure of the material, but also can effectively regulate the particle size of the final positive electrode material to achieve nano-sizing, thereby shortening the ion transmission path and improving the rate performance and cycle performance of the material.

[0051] As a preferred embodiment, the average particle size D50 of the lithium manganese iron phosphate positive electrode material obtained after the crushing is 0.8 μm to 1.6 μm. The specific method of the crushing is not limited in the present invention, and any dry crushing method can be used, such as extrusion, impact, grinding, etc.

[0052] The second aspect of the present invention is to provide a lithium manganese iron phosphate positive electrode material prepared by the preparation method of the carbon-coated lithium manganese iron phosphate positive electrode material as described in the first aspect.

[0053] The third aspect of the present invention is to provide a lithium-ion battery, comprising the lithium iron manganese phosphate positive electrode material as described in the second aspect.

[0054] It is understood that the lithium-ion battery should include a positive electrode, a negative electrode, an electrolyte and a separator, as well as other necessary or unnecessary functional elements or packaging components, etc., and those skilled in the art can make any selection and combination thereof; and the active components of the positive electrode should at least include the lithium iron manganese phosphate positive electrode material, but the selection of other active components in the positive electrode is not excluded. It is understood that when the lithium iron manganese phosphate positive electrode material is included in the lithium-ion battery, it can be regarded as an embodiment of the present invention.

[0055] A fourth aspect of the present invention is to provide an electrical device comprising the lithium-ion battery as described in the third aspect.

[0056] It can be understood that the electrical equipment can be any equipment or device that relies on electric energy to work or operate, including but not limited to new energy vehicles, building electrical equipment, industrial electrical appliances, household and agricultural electrical appliances, etc.; when the lithium-ion battery is included, any electrical equipment equipped with the lithium-ion battery can belong to an embodiment of the present invention.

[0057] Example 1

[0058] (1) The furfural residue was loaded into a dry distillation kettle and placed in an atmosphere furnace, carbonized at 450° C. in a nitrogen atmosphere for 60 min, and cooled to room temperature to obtain a carbonaceous precursor A.

[0059] (2) The carbon precursor A was loaded onto a porous quartz plate and placed in a vertical tube furnace. The temperature was raised to 922°C at a rate of 10°C / min under a nitrogen atmosphere. The nitrogen was then switched to superheated steam to activate the carbon precursor A for 62 minutes before stopping the heating. The carbon-to-water mass ratio was 1:4.5. After activation, the carbon precursor A was cooled to room temperature under a nitrogen atmosphere to obtain furfural residue activated carbon B.

[0060] The specific surface area of ​​the furfural residue activated carbon B obtained in this embodiment was measured by a specific surface area analyzer and was 662.41 m 2 / g. Further Raman analysis was performed on furfural residue activated carbon B. The Raman results showed that furfural residue activated carbon I G / I D =1.03, with a higher degree of graphitization.

[0061] (3) Furfural residue activated carbon B and glucose were weighed at a mass ratio of 0.2:1, and the total amount of the two added was 20wt.% of the amount of ferromanganese phosphate added. First, the furfural residue activated carbon was dispersed in ethanol and added into a sand mill together with glucose. Pure water was added as a dispersion medium, and the mixture was sand-milled for 40 minutes to obtain a dispersion C.

[0062] (4) Weigh ferromanganese phosphate Fe x Mny PO4 (x = 0.3, y = 0.7) and lithium carbonate, and the molar ratio of iron, manganese, phosphorus and lithium is controlled to be Fe: Mn: P: Li = 0.3: 0.7: 1: 1. The above metal salt mixture is added to the dispersion C, and the mass ratio of the two is 4.06: 1, and then the mixing and grinding is continued for 3 hours, and the average particle size D50 of the slurry is ground to 0.4μm, and the slurry D with a solid content of 40% is obtained.

[0063] (5) The slurry D is spray-dried to obtain a lithium iron manganese phosphate spray material. The air inlet temperature during spray drying is 220°C and the air outlet temperature is 95°C. The lithium iron manganese phosphate spray material is loaded into a sagger and placed in a box-type atmosphere furnace. Under a nitrogen atmosphere, the temperature is first raised to 450°C at a rate of 3°C / min and sintered for 3h, and then the temperature is raised to 780°C at a rate of 6°C / min and sintered for 7h. After cooling to room temperature in the furnace, it is taken out and crushed to an average particle size D50 of 1.2μm to obtain the novel biomass activated carbon-carbon-coated lithium iron manganese phosphate positive electrode material E of this embodiment.

[0064] Example 2

[0065] It is basically the same as Example 1, except that:

[0066] The glucose in step (3) is replaced by aspartic acid and citric acid (mass ratio 1:1), and the lithium carbonate in step (4) is replaced by lithium acetate.

[0067] Example 3

[0068] It is basically the same as Example 1, except that:

[0069] In step (4), manganese iron phosphate Fe x Mn y PO4, x=0.5, y=0.5, and the molar ratio of iron, manganese, phosphorus and lithium is controlled to be Fe:Mn:P:Li=0.5:0.5:1:1.

[0070] Example 4

[0071] It is basically the same as Example 1, except that:

[0072] In step (3), furfural residue activated carbon B and glucose are weighed in a mass ratio of 0.5:1.

[0073] Example 5

[0074] It is basically the same as Example 1, except that:

[0075] In step (3), furfural residue activated carbon B and glucose are weighed in a mass ratio of 0.8:1.

[0076] Example 6

[0077] It is basically the same as Example 1, except that:

[0078] The sintering procedure in step (5) is replaced as follows: first, the temperature is raised to 550°C at a rate of 1°C / min and sintered for 4 hours, and then the temperature is raised to 720°C at a rate of 8°C / min and sintered for 10 hours.

[0079] Test example

[0080] The lithium iron manganese phosphate of each of the above embodiments was used to prepare the corresponding test battery, and the specific steps were as follows: the lithium iron manganese phosphate positive electrode material, the conductive agent acetylene black and the binder PVDF prepared in Examples 1 to 6 were weighed in a mass ratio of 90:5:5, and fully stirred, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, and then fully ground and mixed, and then coated on aluminum foil, and vacuum dried at 150°C for 2 hours to form a positive electrode sheet. In a glove box under argon protection, the prepared lithium iron manganese phosphate positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the polyethylene composite film was used as the diaphragm, and 1.0 mol / L lithium hexafluorophosphate was dissolved in ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate (volume ratio of 1:1:1) as the electrolyte, and assembled into a CR2032 button cell as a test battery. At a temperature of 25° C., the button cell was first charged with a constant voltage and constant current, and then charged and discharged at different rates of 2.5V to 4.5V. The electrochemical test of the button cell was performed. The test results are shown in Table 1.

[0081] Table 1

[0082]

[0083] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material, characterized in that: The steps include: (1) subjecting furfural residue to low-temperature carbonization and high-temperature activation in sequence to obtain a first carbon source; (2) preparing a mixed solution comprising the first carbon source and the second carbon source, grinding and obtaining a carbon dispersion; (3) preparing a mixed solution comprising the carbon dispersion, ferromanganese phosphate and a lithium source, grinding and obtaining a slurry; (4) The slurry is spray-dried, sintered and crushed in sequence to obtain a lithium manganese iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The low-temperature carbonization is carried out in an inert gas atmosphere; The temperature of the low-temperature carbonization is 420° C. to 480° C., and the time of the low-temperature carbonization is 45 min to 80 min.

3. The preparation method according to claim 1, characterized in that: The high-temperature activation comprises: placing the material after the low-temperature carbonization in a superheated water vapor atmosphere and letting it stand; The temperature of the high temperature activation is 900° C. to 950° C., and the time of the high temperature activation is 45 min to 80 min.

4. The preparation method according to claim 1, characterized in that: The second carbon source comprises at least one of glucose, sucrose, fructose, polyvinyl alcohol, polyethylene glycol, aspartic acid, citric acid and beta-cyclodextrin; and / or, the lithium source comprises at least one of lithium carbonate, lithium phosphate, lithium hydroxide, lithium sulfate, lithium acetate, lithium dihydrogen phosphate, lithium nitrate and lithium acetate; And / or, the molecular formula of the ferromanganese phosphate is Fe x Mn y PO4, 0.3≤x≤0.7, 0.3≤y≤0.7, x+y=1.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the first carbon source to the second carbon source is (0.2-0.8):

1.

6. The preparation method according to claim 1, characterized in that: The first carbon source comprises at least one of the following properties (a) to (c): (a)I G / I D is 1.0 to 1.2; (b) Specific surface area is 500m 2 / g~800m 2 / g; (c) The electron migration rate is 10 3 S / m~10 6 S / m.

7. The preparation method according to claim 1, characterized in that: The sintering comprises the following steps: First, heat up to 400℃~600℃ at 1℃ / min~3℃ / min, and keep warm for 2h~5h; Then, the temperature is raised to 700°C-800°C at a rate of 5°C / min-10°C / min and kept at this temperature for 7h-10h.

8. The lithium iron manganese phosphate positive electrode material obtained by the method for preparing the carbon-coated lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: Comprising the lithium manganese iron phosphate positive electrode material as described in claim 8.

10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.